Pattern of Hemorrhagic Disorders in Patient with Bleeding Manifestations (IAHS Medical Journal, 2022)
Background: Adults with undiagnosed bleeding disorders present in a variety of ways. While severe bleeding disorders and most congenital bleeding disorders initially present during childhood, conditions associated with heavy bleeding only after a haemostatic challenge (Such as surgery or trauma) often present during adulthood. The evaluation of a patient with a possible bleeding disorder can be one of the most challenging referrals in hematology practice. In the absence of much evidence-based outcomes data, the practitioner’s experimental judgment will be called upon to formulate a working diagnosis and management plan in many instances. The present study is aimed to find out the incidence of diseases presenting with bleeding manifestations and their clinical patterns with age and sex relationship. It is also important to establish the pathological correlation with clinical features.Materials and methods: This observational study was carried out in the Department of Hematology, Armed Forces Institute of Pathology, Dhaka cantonment for a period of one year between 01 January 2018 to 31 December 2018. A total of 57 cases of all ages with bleeding manifestations were studied clinically and appropriate laboratory investigations were carried out to find the causes of bleeding. Statistical analysis was done by using SPSS for windows version 17. c2 test was used as the tests of significance and p value